Glee. The complete second season [videorecording (DVD)]. - Lynch, Jane, 1960-; Michele, Lea; Morrison, Matthew, 1978- (Twentieth Century Fox Home Entertainment, 2011)
"Despite their loss at the Regionals, the kids in New Directions are more motivated than ever. And whether it's Will doing a sexy tango with a substitute teacher, Sue joining the glee club, or everyone catching Bieber fever, the excitement at William McKinley High School is keeping everyone on their toes."--Container.